Listen to the data when results are not significant - Hewitt, Catherine E (BMJ Publishing Group Ltd., 2008)
Unexpected non-significant results from randomised trials can be difficult to accept. Catherine Hewitt, Natasha Mitchell, and David Torgerson find that some authors continue to support interventions despite evidence that they might be harmful